SYNTHESIS AND CHARACTERIZATION OF CHITOSAN- GRAFT-ACRYLAMIDE FOR ENHANCED OIL RECOVERY APPLICATION - Ratihningtias Yulianti, Cempaka
Enhanced Oil Recovery method can enhance oil recovery and stabilize oil production by injecting material into the reservoir. One of the technique in Enhanced Oil Recovery is polymer flooding. In this research, graft copolymerization of chitosan with acrylamide has been synthesized which the first stage is isolation of chitin from shrimp shell waste and synthesis of chitosan. Chitosan-graft-acrylamide (K-g-AM) has been successfully synthesized and shown to be optimal copolymerization is grafting degree to 279.101%, intrinsic viscosity of K-g-AM to 958.3 mL/g, and dynamic viscosity of K-g-AM in 5000 ppm to 15.639 cP. Based on rheological measurements, K-g-AM has better resistance to temperature, shear rate, and salinity in comparison with commercial polymer, HyboMax®. Based on thermal analysis using method of Differential Scanning Calorimetry-Thermo Gravimetric Analysis, K-g-AM has glass transition temperature (Tg) at 107.1 ?C to 125.6 ?C, crystallization point (Tc) at 210.9 ?C, and melting point (Tm) at 242 ?C. Therefore, glass transition temperature (Tg) and melting point (Tm) of K-g-AM is higher than chitosan and polyacrylamide because of forming copolymer with high molecular mass.